Preliminary Research: Development of Digital Student Worksheets Based on Indonesian Realistic Mathematics Education To Improve Deaf Students' Understanding of Mathematical Concepts - Boru, Mariana Sanita; Ambarwati, Lukita; Hidajat, Flavia Aurelia (Universitas Wiralodra, 2024)
Understanding mathematical concepts is an essential basis for thinking in solving mathematical and real world problems. However, students still do not understand mathematical concepts. The low ability to understand mathematical concepts is not only limited to normal students, but is also experienced by students with special needs, namely the deaf. Therefore, mathematics learning must be focused on improving a person's ability to understand concepts. The aim of this research is to develop Student Worksheets (LKPD) using the Indonesian Realistic Mathematics Approach (PMRI) to improve the ability to understand mathematical concepts for deaf students. The method used is research and development with the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). At the analysis and design stage, data is collected through observation, questionnaires, interviews and tests. Next, the data is processed descriptively and quantitatively. Findings from the analysis results show that one of the subjects considered difficult by deaf students is whole numbers. This is caused by teaching materials that do not suit their characteristics. The results of the test for the ability to understand mathematical concepts show that the average score obtained by students is 53.20 and is categorized as low. Only one in six students meets the minimum completion requirement of 65 set by the school. Therefore, this research can be continued by developing PMRI-based digital LKPD to improve the ability to understand mathematical concepts. This is because the PMRI-based digital LKPD includes various stimuli carried out through various media, such as pictures, readings and videos and the contents of the LKPD have been summarized from several sources and presented using an approach that starts from the context of students' daily lives and continues with mathematics learning. formal. Another advantage is that this LKPD can be accessed at any time so it is easier for students to understand it.